Identification of Contractual and Financial Dispute Causes in the Off-Site Construction Projects - Yildiran, Merve Pelinsu; Demirdogen, Gokhan (MDPI, 2024)
Off-site construction (OFC) is a hot topic to remedy the chronic issues of the construction industry, such as low levels of productivity, waste, safety risks, environmental pollution, poor quality, and time and cost issues. However, the lack of standards and knowledge about OFC projects hamper the adaptation process. Disputes are one of the most important hampering factors. Therefore, this study aims to identify contractual and financial disputes and to detect the importance level of disputes in OFC projects. In the study, the Focus Group Discussion (FGD) technique, Pythagorean fuzzy AHP, and fuzzy TOPSIS were employed. As a result of FGD, 42 dispute causes for off-site construction projects were found. The Pythagorean fuzzy AHP method was used to calculate the weights of the criteria (occurrences, severity, and detection) that were used in the evaluation of dispute causes. The Pythagorean fuzzy AHP analysis results indicated that detection is more important than other criteria in the evaluation of off-site construction dispute causes. After that, the fuzzy TOPSIS method was used to determine the importance level of off-site construction dispute causes. The analysis results showed that Increase in contract value due to revision in scope of work in the contractual factor group and Extra money for the additional works in the financial factor group are the most important dispute causes, respectively. The study findings can be used for the evaluation and analysis of OFC project contracts.
Keywords: off-site construction; financial disputes; contractual disputes; PYTHAGOREAN FUZZY AHP; RISK-ASSESSMENT; TOPSIS; MANAGEMENT; ALLOCATION; FRAMEWORK; SELECTION; COST; Construction & Building Technology; Engineering